Assessing the quality of primary care referrals to surgery of patients with diabetes in the East of England: A multi‐centre cross‐sectional cohort study. Issue 7 (15th June 2017) - Pournaras, Dimitri J.; Photi, Evangelos S.; Barnett, Nicholas; Challand, Christopher P.; Chatzizacharias, Nikolaos A.; Dlamini, Nokwanda P.; Doulias, Triantafyllos; Foley, Aoibhinn; Hernon, James; Kumar, Bhaskar; Martin, Jack; Nunney, Ian; et al.
Summary: Aim: Peri‐operative hyperglycaemia is associated with an increased incidence of adverse outcomes. Communication between primary and secondary care is paramount to minimise these harms. National guidance in the UK recommends that the glycated haemoglobin (HbA1c) should be measured within 3 months prior to surgery and that the concentration should be less that 69 mmol/mol (8.5%). In addition, national guidance outlines the minimum dataset that should be included in any letter at the time of referral to the surgeons. Currently, it is unclear how well this process is being carried out. This study investigated the quality of information being handed over during the referral from primary care to surgical outpatients within the East of England. Methods: Primary care referrals to nine different NHS hospital Trusts were gathered over a 1‐week period. All age groups were included from 11 different surgical specialties. Referral letters were analysed using a standardised data collection tool based on the national guidelines. Results: A total of 1919 referrals were received, of whom 169 (8.8%) had previously diagnosed diabetes mellitus (DM). However, of these, 38 made no mention of DM in the referral letter but were on glucose‐lowering agents. Only 13 (7.7%) referrals for patients with DM contained a recent HbA1c, and 20 (11.8%) contained no documentation of glucose‐lowering medication. Conclusion: This study has shown that the quality of referral letters to surgical specialties for patients with DM in the East of England remain inadequate. There is a clear need for improving the quality of clinical data contained within referral letters from primary care. In addition, we have shown that the rate of referral for surgery for people with diabetes is almost 50% higher than the background population with diabetes.